FOOD PRODUCT PURCHASE DECISION BEHAVIOR HALAL CERTIFIED - Muhammad Arif; Andri Soemitra (Proceeding International Seminar of Islamic Studies, 2022)
Islam is very strict about eating and drinking that is obtained and consumed. This affirmation can be seen in various verses which state that there is an impact given when Muslims eat food that is breed and is not good. Public trust has grown with the presence of a halal logo on every product, a fact found in this study that people really care about what they consume. Because it is believed that what is consumed will have an influence on what is being carried out daily. People's confidence to buy products is due to the logo listed on each package. This study aims to describe the existing literature and present the decision to purchase halal food products. This research approach is qualitative content analysis with the type of literature study. This study uses secondary data such as articles, research results, and reference books. The results of the study found that research related to Halal Food Products in buying interest from 2018 to 2022 only found 58 articles. Halal food products will provide more optimal benefits if followed by public awareness.